Coefficient Inequalities for $p$-Valent Functions (Analysis in Theory and Applications, 2018)
In the present paper, the authors introduce a new subclass of $p$-valent analyticfunctions with complex order defined on the open unit disk $\mathbb{U}=\{z:z∈\mathbb{C}\ \text{and}\ |z|
Keywords: $p$-valent function; subordination; coefficient inequalities; convolution.